Perception and disposition to digital rectal examination in the prevention of prostate cancer - Paredes Ajalla, Albert Mijail (2022)
Introduction. Prostate cancer can be detected by digital rectal examination. Objectives. To explore the perception and disposition to digital rectal examination. Methods. A qualitative study was carried out. The unit of analysis was the patient who comes to the service’s outpatient consultation. An in-depth interview was used. Results. The perception of digital rectal examination has as a priori categories that are machismo, homosexuality, shame, pain and sexual impotence. The emerging category was predisposition to digital rectal examination in the urology service, predisposition due to the benefit of performing digital rectal examination, and predisposition of patients who had already undergone digital rectal examination. Conclusions. The perception has emerging categories such as the predisposition to digital rectal examination in patients of the urology service, predisposition of patients who had a previous consultation. The willingness to digital rectal examination is accepted by patients as it is a medical indication performed by a trained professional.